Model Pengembangan Bisnis Pukat Cincin Skala Kecil Berkelanjutan Pada KM Pricilia di Desa Latta, Kota Ambon - Simon Marsholl Picaulima; Meyske Angel Rahantoknam; Sona Sonia Reneuw; Baleta Jamlean; Sandra Yani Rettob; Aditiya Bakri (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The small-scale purse seine business at KM Priscilia in Latta Village, Ambon City since its establishment in 2002 until now has not been able to grow rapidly, due to the lack of education and implementation that results in a business development strategy that can be applied, while the number of small-scale purse seine fleets in Ambon City since 2017 until now continues to increase. Therefore, the small-scale purse seine business at KM Priscilia must improve the current business development strategy model for the sustainability of the business. The purpose of this study is to identify the current small-scale purse seine business model and evaluate and design new and sustainable business development strategy models. This research was conducted from November 2022 to February 2023 with a case study approach on KM Priscilia's small-scale purse seine business in Latta Village. The data analysis used is qualitative descriptive, namely Business Model Canvas (BMC) and SWOT analysis. The results of this study show that the current business model at KM Priscilia based on the analysis of the nine elements of the business model canvas still needs improvement, and the results of the SWOT analysis produce alternative development strategies for SO there are 3, WO there are 4, ST there are 4 and WT there are 3 as the basis for the preparation of the four prototypes of KM Priscilia's sustainable business canvas business model.